Pandangan Paulus tentang bekerja yang professionaldalam 2 Tes 3: 10 dan aplikasinya bagi orang Kristen masa kini - Abatan, Yofince (STPK St. Yohanes Rasul Jayapura, 2025)
Work is an essential aspect of human life and is often associated with the pursuit of well-being. However, many fail to recognize that work is not solely oriented toward material fulfillment but also carries a significant spiritual dimension. This study aims to reveal the theological values of work based on 2 Thessalonians 3:10, which reflects the Apostle Paul's teaching on the responsibility of labor within the Christian faith. The research employs a literature study method with an exegetical approach to the text of 2 Thessalonians 3:10, focusing on the Greek verb ergazesthai, the infinitive form of ergazomai, which signifies working actively and responsibly. The findings show that although Paul does not explicitly use modern terminology such as